2022
DOI: 10.1038/s41598-022-08492-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vascular endothelial growth factor (VEGF) level in the tears and serum of age-related macular degeneration patients

Abstract: Age-related macular degeneration (AMD) is an important cause of irreversible central blindness worldwide. Clinical manifestations range from asymptomatic in early and intermediate AMD to significant vision loss in late AMD. Approximately 10% of cases of early AMD eventually progress to the late advanced stage, influenced by the upregulation of vascular endothelial growth factor (VEGF). In this study, we evaluated VEGF concentration in the tears and serum of AMD patients. Our study revealed a significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Additionally, recently, VEGF levels in tears and serum were simultaneously measured in the same cohort of patients [ 69 ]. The cohort was composed of 108 individuals split into three categories (early AMD, late AMD and controls), each of which contained a third of the patients.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, recently, VEGF levels in tears and serum were simultaneously measured in the same cohort of patients [ 69 ]. The cohort was composed of 108 individuals split into three categories (early AMD, late AMD and controls), each of which contained a third of the patients.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that the contents of tear uids not only re ect the health of the ocular surface but also provide insights into the intraocular environment [12,13]. VEGF concentrations in tear uid have been found to associate with the severity of macular edema in retinal vein occlusion [38], the clinical stage of diabetic retinopathy [39], and the severity of age-related macular degeneration [40]. As a result, it has proven useful in monitoring diseases involving angiogenesis in adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…No findings Yes [184] Yes [178] Yes [185] Treatment [186]. The increasing prevalence of DR is linked to the rise in cases of diabetes associated with the increasing prevalence of obesity and sedentary lifestyles [187].…”
Section: Vegfmentioning
confidence: 99%